Prototype Curriculum: Opportunities and Challenges of Inclusive Schools in Implementing Education for All in the Metaverse Era - Bakhri, Syamsul; Sofyan, M. Ali (Muslim Education Review, 2022)
During the COVID-19 pandemic, both special and inclusive schools can implement the 2013 curriculum, the emergency curriculum, and the prototype curriculum. The prototype curriculum is a new opportunity because it focuses on developing students’ soft skills and character. However, it also challenges developing metaverse technology in its accessibility for students with special needs. This study uses a qualitative method with a literature study approach and content analysis techniques. The results were analyzed using Pierre Bourdieu’s theory of social practice. The research results show that the prototype curriculum in special schools or special education focuses on developing soft skills and students’ character. There is an opportunity for inclusive schools to be a fair arena for all students. If the development of metaverse technology increases the accessibility of students with special needs then the implementation of inclusive education will be achieved because in cyberspace everyone has the same equality and accessibility. The challenges faced by inclusive schools are government policies that have not implemented inclusive education thoroughly and evenly; the inclusive education curriculum which now has to adapt to the prototype curriculum; lack of facilities and infrastructure; teacher training that has not been maximized; lack of community understanding; and technical problems in the implementation of inclusive education.